2008
DOI: 10.1007/s11269-008-9325-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Withdrawal on Hydrodynamics of a Stratified Reservoir

Abstract: In water supply reservoirs, selective withdrawal is commonly implemented to control released water temperature for quality purposes. This study investigated the effects of selective withdrawal on hydrodynamics of a stratified reservoir through numerical modeling and analytical analysis. A 3-D hydrodynamic model was applied where observations of water temperature time series recorded every 30 min at the thermocline and measured temperature profiles along the water column were used to validate the numerical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 23 publications
2
47
0
1
Order By: Relevance
“…It has been recommended as a tool for the development of the Total Maximum Daily Load by the US Environmental Protection Agency (1997) (US Environmental Protection Agency, 1997). The EFDC is an integrated modeling system that has been widely used for a wide range of environmental studies including simulating hydrodynamics, thermal stratification, water age, transport, Langrangian particle tracers and eutrophication processes in rivers, lakes, estuaries, reservoirs, wetlands and coastal regions (Çalışkan and Elçi, 2009;Gong et al, 2009;Hamrick, 1992;He et al, 2011;Li et al, 2009a;Li et al, 2013). The hydrodynamics of the EFDC is based on the Princeton Ocean Model (Blumberg and Mellor, 1987).…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…It has been recommended as a tool for the development of the Total Maximum Daily Load by the US Environmental Protection Agency (1997) (US Environmental Protection Agency, 1997). The EFDC is an integrated modeling system that has been widely used for a wide range of environmental studies including simulating hydrodynamics, thermal stratification, water age, transport, Langrangian particle tracers and eutrophication processes in rivers, lakes, estuaries, reservoirs, wetlands and coastal regions (Çalışkan and Elçi, 2009;Gong et al, 2009;Hamrick, 1992;He et al, 2011;Li et al, 2009a;Li et al, 2013). The hydrodynamics of the EFDC is based on the Princeton Ocean Model (Blumberg and Mellor, 1987).…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…If we treat the lake or reservoir as a control volume, the thermodynamics is mainly governed by meteorological conditions that determine the surface heat flux [16][17][18][19][20], the heat exchange with sediment bed, and the inflows and outflows of the reservoir [21][22][23][24]. A reservoir differs from a natural lake due to its dynamic outflows associated with reservoir regulation [12,[24][25][26][27][28][29]. A reservoir typically has inflows varying with the season (dry or wet periods).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the CE-QUAL-W2 model was determined to be the most suitable model for analyzing the turbidity current because it was necessary to analyze the dynamics of sinking, floating, and resurfacing particles. In addition, the model can accurately simulate stratification phenomena, density current flow, vertical mixing around the water body to accurately analyze the movement of a turbidity current inflow of a reservoir [7,[20][21][22][23][24]. The application of a 2-dimensional model is advantageous for analyzing the effectiveness of selective intake facilities because this is required for analyzing changes in movement caused by turbidity current.…”
Section: Model Selection and Descriptionmentioning
confidence: 99%
“…The efficiency of engineering approaches like selective withdrawal, flushing, blocking curtains or de-stratification for simulating high turbidity issues in a reservoir cannot be assessed with 3-D models like the hydrostatic assumption. Because the engineering methods probably include a significant vertical acceleration, the 3-D models using a hydrostatic assumption cannot provide accurate simulation for the complex movement of engineering approaches that produce a significant vertical acceleration [22][23][24]. Therefore, we concluded that CE-QUAL-W2 was more suitable than 3-D models for this study.…”
Section: Introductionmentioning
confidence: 97%